Assessment of readiness to transition from antenatal HIV surveillance surveys to PMTCT programme data-based HIV surveillance in South Africa: The 2017 Antenatal Sentinel HIV Survey. (February 2020) - Woldesenbet, Selamawit A.; Kufa, Tendesayi; Barron, Peter; Ayalew, Kassahun; Cheyip, Mireille; Chirombo, Brian C.; Lombard, Carl; Manda, Samuel; Pillay, Yogan; Puren, Adrian J.
Highlights: Agreement between point-of-care rapid testing and laboratory-based HIV testing was high. PMTCT uptake was high (>99%). Selection bias with using programme data was low (0.3%). Abstract: Objective: South Africa has used antenatal HIV surveys for HIV surveillance in pregnant women since 1990. We assessed South Africa's readiness to transition to programme data based antenatal HIV surveillance with respect to PMTCT uptake, accuracy of point-of-care rapid testing (RT) and selection bias with using programme data in the context of the 2017 antenatal HIV survey. Methods: Between 1 October and 15 November 2017, the national survey was conducted in 1, 595 public antenatal facilities selected using stratified multistage cluster sampling method. Results of point-of-care RT were obtained from medical records. Blood samples were taken from eligible pregnant women and tested for HIV using immunoassays (IA) in the laboratory. Descriptive statistics were used to report on: PMTCT uptake; agreement between HIV point-of-care RT and laboratory-based HIV-1 IA; and selection bias associated with using programme data for surveillance. Results: PMTCT HIV testing uptake was high (99.8%). The positive percent agreement (PPA) between RT and IA was lower than the World Health Organization (WHO) benchmark (97.6%) at 96.3% (95% confidence interval (CI): 95.9%–96.6%). The negative percent agreement was above the WHO benchmark (99.5%), at 99.7% (95% CI: 99.6%–99.7%) nationally. PPA markedly varied by province (92.9%–98.3%). Selection bias due to exclusion of participants with no RT results was within the recommended threshold at 0.3%. Conclusion: For the three components assessed, South Africa was close to meeting the WHO standard for transitioning to routine RT data for antenatal HIV surveillance. The wide variations in PPA across provinces should be addressed.